Chronic sleep deprivation altered the expression of circadian clock genes and aggravated Alzheimer's disease neuropathology. (20th October 2021) - Niu, Long; Zhang, Feng; Xu, Xiaojiao; Yang, Yuting; Li, Song; Liu, Hui; Le, Weidong
Abstract: Circadian disruption is prevalent in Alzheimer's disease (AD) and may contribute to cognitive impairment, psychological symptoms, and neurodegeneration. This study aimed to evaluate the effects of environmental and genetic factors on the molecular clock and to establish a link between circadian rhythm disturbance and AD. We investigated the pathological effects of chronic sleep deprivation (CSD) in the APP swe /PS1 ΔE9 transgenic mice and their wild‐type (WT) littermates for 2 months and evaluated the expression levels of clock genes in the circadian rhythm‐related nuclei. Our results showed that CSD impaired learning and memory, and further exaggerated disease progression in the AD mice. Furthermore, CSD caused abnormal expression of Bmal1, Clock, and Cry1 in the circadian rhythm‐related nuclei of experimental mice, and these changes are more significant in AD mice. Abnormal expression of clock genes in AD mice suggested that the expression of clock genes is affected by APP/PS1 mutations. In addition, abnormal tau phosphorylation was found in the retrosplenial cortex, which was co‐located with the alteration of BMAL1 protein level. Moreover, the level of tyrosine hydroxylase in the locus coeruleus of AD and WT mice was significantly increased after CSD. There may be a potential link between the molecular clock, Aβ pathology, tauopathy, and the noradrenergic system. The results of this study provided new insights into the potential link between the disruption of circadian rhythm and the development of AD. Abstract : CSD exaggerated disease progression in the AD mice. After CSD, the abnormal expression of clock genes in AD mice pineal gland, LC and RSC may be related to the dysfunction of SCN. The level of tyrosine hydroxylase in the locus coeruleus of AD and WT mice was significantly increased after CSD. There may be a potential link between the molecular clock, Aβ pathology, tauopathy, and noradrenergic system.